Nb-doped layered FeNi phosphide nanosheets for highly efficient overall water splitting under high current densities. Issue 15 (9th April 2021) - Wen, Shuting; Chen, Guangliang; Chen, Wei; Li, Mengchao; Ouyang, Bo; Wang, Xingquan; Chen, Dongliang; Gong, Teng; Zhang, Xianhui; Huang, Jun; Ostrikov, Kostya (Ken)
Abstract : A double-layered trimetallic phosphide of Ni12 P5 –Fe2 P–NbP is engineered on plasma-treated nickel foam, and its overpotentials for the HER and OER are only 265 and 330 mV at j 400 respectively, as well as showing a low cell voltage of 1.65 V at j 100 . Abstract : Nanostructured trimetallic phosphide electrocatalysts are promising for H2 and O2 evolution reactions (HER/OER) that are actively pursued nowadays to achieve commercial hydrogen production. Herein, a dual-functional Nb-doped NiFe phosphide nanosheet catalyst with a low cost and high stability was successfully prepared on nickel foam (NF) pretreated with dielectric barrier discharge (DBD) plasmas (PNF) operated under ambient conditions. The resulting Ni12 P5 –Fe2 P–NbP layered nanosheets on the PNF show exceptional catalytic performances, evidenced by their low overpotentials for delivering current densities of 100 and 400 mA cm −2 ( j 100 / j 400 ) of only 178 and 265 mV for the HER, and 280 and 330 mV for the OER, as well as the small Tafel slope values of 52 (HER) and 59 (OER) mV dec −1, respectively. The catalyst also exhibits a good electrocatalytic durability and stability during 100 h continuous HER and OER tests at j 300 . Moreover, the current densities of 10 and 100 mA cm −2 are achieved at low cell voltages of 1.51 and 1.65 V, thus outperforming most of the reported electrocatalysts in two-electrode alkaline water electrolyzers. Numerical simulation analysis shows that the Ni and Nb atoms in the Ni12 P5 –Fe2 P–NbP nanostructures are the key factors responsible for the achieved excellent performance in water electrolysis.